A wish to die among Japanese university freshmen: its association with the sense of coherence and relationship with parents and close friends - Ahmad Basri, Nadzirah; Honda, Takanori; Chen, Sanmei; Supartini, Atin; Hirano, Yuko; Kumagai, Shuzo (Japanese Society of Health Promotion, 2017)
Background: Suicide is the leading cause of death among youths in Japan. The identification of factors associated with a wish to die may provide insights into prevention of suicide. Objectives: The goals of this study were to examine the association between the sense of coherence (SOC), relationship with parents and close friends and motivation in studies with a wish to die, independent of depressive symptoms among Japanese university freshmen. Methods: We used the baseline data of freshmen from a mental health study in a Japanese public university (N=2,036). We conducted multiple logistic regression analyses to predict the contribution of the SOC, relationship with parents and close friends and motivation in studies to a wish to die among freshmen. Results: Higher SOC was associated with lower odds of having a wish to die, independent of depressive symptoms. Having a good relationship with one’s parents and the absence of close friends were respectively associated with lower and higher odds of having a wish to die. Conclusion: These findings provided insights into the importance of the SOC scale that may be used by school clinicians to screen and target students who may be at risk of suicide. The enhancement of interpersonal skills of students is also important to prevent a wish to die among students.